TAP BLOCK VERSUS WOUND INFILTRATION IN SUBJECTS WITH GYNECOLOGICAL SURGERIES - Nidhi Chaturvedi, Dr. (International Journal of Psychosocial Rehabilitation, 2010)
BACKGROUND: Transversus abdominis plane (TAP) block and wound infiltration (WI) with local anaesthetics are used for postoperative analgesia following gynaecological surgeries, reducing the need for administration of opioids.OBJECTIVE OF THE STUDY: The objective of our study was to assess the post-operative relief of pain in subjects who receive TAP block versus local wound anaesthetic infiltration with 0.25% bupivacaine following open gynaecological surgeries, using visual analogue scale at rest and movement.METHODS: We included a total of 100 cases based on inclusion and exclusion criteria. TAP block was administered in 50 subjects who underwent gynecological procedures and local wound infiltration was administered in 50 subjects who underwent gynecological procedures.RESULTS: it is quite evident that the post-operative VAS scores were significantly reduced in subjects with TAP block compared to the VAS scores in the subjects with local wound infiltration.CONCLUSIONS: The TAP block is more effective and safe technique for postoperative analgesia for lower abdominal gynaecological surgeries, compared to the surgical wound infiltration.